2006
DOI: 10.1080/08860220600583625
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition–Inflammation–Atherosclerosis (MIA) Syndrome Components in Hemodialysis and Peritoneal Dialysis Patients

Abstract: Before choosing renal replacement therapy, malnutrition, inflammation, and atherosclerosis parameters must be investigated in ESRD patients. Hemodialysis seems to be more advantageous for malnutrition components than CAPD. Both dialysis modalities seem to be similar for inflammation, and CAPD modality has superiority for atherosclerosis. Before choosing the type of renal replacement therapy, assessment of MIA syndrome components could be useful for individualization of the decision on which dialytic modality i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
47
1
9

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 40 publications
6
47
1
9
Order By: Relevance
“…Other studies found hyperlipidemia more frequently in CAPD patients than in HD patients. 13,14,16 But in our study there was no statistically significant differences between HD and CAPD groups according to lipid and apolipoprotein levels except Lp(a), supporting results reported in the literature. 15,[20][21][22] Correlations between high Lp(a) and ischemic cardiovascular disease, cerebrovascular disease, and peripheral vascular disease have been documented in many reports.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Other studies found hyperlipidemia more frequently in CAPD patients than in HD patients. 13,14,16 But in our study there was no statistically significant differences between HD and CAPD groups according to lipid and apolipoprotein levels except Lp(a), supporting results reported in the literature. 15,[20][21][22] Correlations between high Lp(a) and ischemic cardiovascular disease, cerebrovascular disease, and peripheral vascular disease have been documented in many reports.…”
Section: Discussionsupporting
confidence: 82%
“…7 Many studies have found CAPD patients to have a more atherogenic lipoprotein profile than do HD patients. [13][14][15] However, studies of the HD population have not identified elevated plasma lipids as the principal risk factor for coronary artery atherosclerosis. 19 In our study, plasma TG, Lp(a), and Apo B levels of patients with ESRD were significantly increased over those in the control group; however, HDL, Apo A-I, albumin, and Apo E levels were decreased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Malnutrition, inflammation, atheroscleosis/calcification (MIAC) syndrome has been defined as the interaction between increased levels of proinflammatory cytokines, malnutrition, and atherosclerosis/calcification in ESRD patients (5,6). The presence of MIA components was found to be associated with increased mortality and morbidity in ESRD patients receiving PD (7) or HD (8). The coronary artery calcification score (CACS) in patients with ESRD reflects the severity of atherosclerotic vascular disease and predicts cardiovascular events (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Malnütrisyon göstergeleri HD alan grupta daha iyi seyrederken, PD nin ateroskleroz gelişimini önlemede daha etkin olduğu görülmüştür. Bu nedenle tedaviye karar vermeden önce MIA sendromunun bileşenlerinin ayrı ayrı değerlendirilmesi ve bireysel karar verilmesi gerekliliği bildirilmiştir (47). Bir başka çalışmada KVH için en önemli risk faktörlerinden biri olan kronik inflamasyon aterosklerozis gelişimini hızlandırmaktadır (31,32).…”
Section: Mıa Sendromunun Tedavisinde Yeni Stratejilerunclassified